Experimental study of expression profile and specific role of human microRNAs in regulating atrophic bone nonunion. Issue 36 (4th September 2020) - Wei, Junqiang; Chen, Hua; Fu, Yangmu; Zhang, Boxun; Zhang, Lihai; Tao, Sheng; Lin, Feng
Abstract : Abstract: The expression profile and specific roles of microRNAs (miRNAs) in regulation of atrophic bone nonunion are not fully understood. Here, we present evidence that miRNAs are involved in regulation of several osteogenic genes and may contribute to the development of atrophic bone nonunion. The miRNA expression profile of repairing tissues in atrophic bone nonunion patients (group A) and in callus tissues from patients with healed fractures (group B) were quantitatively measured. microRNA microarrays were used to identify differentially expressed miRNAs, and the bioinformatics methods were used to predict the potential target genes. Quantitative real-time polymerase chain reaction (qRT-PCR), western blot, and dual-luciferase reporter assay were performed in human bone marrow stromal cells (hBMSCs) to validate the microarray results. Nine miRNAs in group A were up-regulated 1.5 times compared to group B, while the other 9 miRNAs in group A were down-regulated 1.5 times. Several target regions of these miRNAs were identified in the osteogenic genes, as well as in the other genes in their families or related regulatory factors. Four miRNAs (hsa-miR-149 *, hsa-miR-221, hsa-miR-628-3p, and hsa-miR-654-5p) could play important roles in regulating bone nonunion development. hBMSCs transfected with these miRNAs significantly decreased mRNA levels of alkaline phosphatase, liver/bone/kidney ( ALPL ), platelet derived growth factor subunit A ( PDGFA ), and bone morphogenetic protein 2 ( BMP2 ). Lower protein expression levels were observed using western blotting, confirming that ALPL, PDGFA, and BMP2 were directly targeted by hsa-miR-149 *, hsa-miR-221, and hsa-miR-654-5p, respectively. In summary, hsa-miR-149 *, hsa-miR-221, and hsa-miR-654-5p may play important biological roles by repressing osteogenic target genes ALPL, PDGFA, and BMP2, and, therefore, contributing to progression of atrophic bone nonunion.